Odpowiedź :
a) A=(5,+∞)
b) B= (-∞,7) u <2,+∞)
c) C= (-∞,6>
d) D= (-∞,5) u (5,+∞)
e) E= (-∞, -5) u (-5, -1) u (-1,+∞)
f) F= (-∞, 0> u (2, +∞)
Ewentualnie
a) x∈ (5,+∞)
b) x∈ (-∞,7) u <2,+∞)
c) x∈ (-∞,6>
d) x∈ (-∞,5) u (5,+∞)
e) x∈ (-∞, -5) u (-5, -1) u (-1,+∞)
f) x∈ (-∞, 0> u (2, +∞)
b) B= (-∞,7) u <2,+∞)
c) C= (-∞,6>
d) D= (-∞,5) u (5,+∞)
e) E= (-∞, -5) u (-5, -1) u (-1,+∞)
f) F= (-∞, 0> u (2, +∞)
Ewentualnie
a) x∈ (5,+∞)
b) x∈ (-∞,7) u <2,+∞)
c) x∈ (-∞,6>
d) x∈ (-∞,5) u (5,+∞)
e) x∈ (-∞, -5) u (-5, -1) u (-1,+∞)
f) x∈ (-∞, 0> u (2, +∞)
a) (5,+∞)
b) (-∞,-7) u <2,+∞)
c) (-∞,6>
d) (-∞,5) u (5,+∞)
e) (-∞, -5) u (-5,-1) u (-1, +∞)
f) (-∞,0> u (2, +∞)
b) (-∞,-7) u <2,+∞)
c) (-∞,6>
d) (-∞,5) u (5,+∞)
e) (-∞, -5) u (-5,-1) u (-1, +∞)
f) (-∞,0> u (2, +∞)